Local Wisdom in The Process of Criminal Law Enforcement in Papua (Case Study Of Handling Criminal Actions Preceded by Traditional Fine in Wamena, Jayawijaya District) - Arsensius, Ricarda; Prasetyo, Handoyo; Wahyudi, Slamet Tri (PT. Hafasy Dwi Nawasena, 2024)
Papua has vital ethnic, cultural and local wisdom. Indigenous communities in Papua have a legal system and social institutions that have been passed down from generation to generation, including resolving conflicts or violations through the mechanism of customary fines (compensation) imposed by customary institutions. In some cases, customary fines imposed by customary institutions for acts categorized as criminal acts in national law are a consideration for law enforcement officials in handling these cases. This shows the integration between customary law and national criminal law in the law enforcement process in Papua. This research aims to determine the impact and contribution of local wisdom in law enforcement in Papua, especially in handling criminal acts involving customary fines. This local wisdom-based approach allows for a more peaceful resolution, focuses on togetherness, and is considered fairer by all parties involved. Traditional heads and traditional institutions play an essential role in mediating and determining the appropriate amount of fines, with deliberation being the key to reaching a fair agreement.